Characteristics of symptom distress in Chinese nasopharyngeal carcinoma patients and its relation to mood disturbance: A cross‐sectional study. (11th March 2019) - Chen, Yu; Chen, Weichen; Yang, Yuan; Zhao, Yang; Yang, Xueling
Abstract: Objective: To evaluate the psychometric properties of a modified Chinese version of the Symptom Distress Scale (SDS), to explore symptom distress and its association with mood disturbance and factors that related to levels of symptom distress and mood disturbance. Methods: A cross‐sectional, correlation design was adopted. A convenience sample of 190 nasopharyngeal carcinoma (NPC) patients was recruited from a Cancer Center in Guangzhou, China, with 169 patients completing the study. Results: The psychometric properties of the modified SDS were satisfactory (Cronbach's α = 0.80) with test–retest reliability (correlation coefficient = 0.71). Education, marital status, disease stage and SDS scores were significant influencing factors of mood disturbance. The overall symptom distress level of NPC patients was higher than that of other cancer groups, with dry mouth being the most distressing symptom. Symptom distress level was influenced by age, marital status, disease stage, treatment modality and number of radiotherapy (RT) sessions. Conclusion: More pain and symptom management care should be focused on patients who are older, single or divorced patients, those with late‐stage disease, and those subjected to multimodality therapy. Symptom distress was the most significant influencing factor of NPC patients' mood status.